1997
DOI: 10.1094/pdis.1997.81.10.1187
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effect of Temperature and Triadimefon on Proliferation of Uncinula necator: Implications for Fungicide Resistance and Disease Risk Assessment

Abstract: Triadimefon has been used in California to control Uncinula necator, causal agent of grape powdery mildew, since 1982. Instances of unsatisfactory control have occurred mainly in the cooler coastal areas of California. The effect of temperature and application of triadimefon was investigated over a 53-day-period on two U. necator isolates, sensitive and resistant to triadimefon. At 15°C, 25°C, or temperatures fluctuating between 15 and 25°C, in absence of triadimefon, the isolates continued to produce high num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…In our controlled-environmental experiments, we found that E. necator continued to germinate, grow, and sporulate at higher temperatures than previously reported (10,11,36). Erom 30 to 34°C, we showed that temperature is not lethal to three of the major stages of the pathogen's asexual life cycle, although long exposure times (up to 24 h) at these temperatures reduced growth and reproduction.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…In our controlled-environmental experiments, we found that E. necator continued to germinate, grow, and sporulate at higher temperatures than previously reported (10,11,36). Erom 30 to 34°C, we showed that temperature is not lethal to three of the major stages of the pathogen's asexual life cycle, although long exposure times (up to 24 h) at these temperatures reduced growth and reproduction.…”
Section: Discussionsupporting
confidence: 52%
“…As an obligate parasite, E. necator cannot be grown on defined media but it responds well to a variety of leaf and leaf disk systems with and without agar (30,36). Grapevines {Vitis vinifera) of the highly susceptible 'Carignane' were raised in a glasshouse to provide a year-round source of young, disease-free leaves for controUed-environment experiments and to maintain E. necator isolates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For polycyclic fungal pathogens, abiotic conditions (i.e., temperature, rainfall, surface wetness, and relative hu-midity) are generally thought to drive the rate at which an epidemic develops (Agrios 1997). For grape powdery mildew, temperature and humidity are particularly important (Delp 1954, Ypema and Gubler 1997, Carroll and Wilcox 2003. Our results illustrate a heretofore unappreciated impact of predation on fungal population dynamics.…”
Section: Discussionmentioning
confidence: 71%